2022
DOI: 10.1038/s41598-022-24255-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of climate on surgical site infections and anticipated increases in the United States

Abstract: Surgical site infections (SSI) are one of the most common and costly hospital-acquired infections in the United States. Meteorological variables such as temperature, humidity, and precipitation may represent a neglected group of risk factors for SSI. Using a national private insurance database, we collected admission and follow-up records for National Healthcare Safety Network-monitored surgical procedures and associated climate conditions from 2007 to 2014. We found that every 10 cm increase of maximum daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In a data set of 1.6 million infections due to Escherichia coli, Klebsiella pneumoniae , and Staphylococcus aureus , they identified significant associations between antimicrobial resistance patterns in these common pathogens and higher local minimum temperatures. 24 Another recent study similarly showed modest but significant impacts of both local temperature and humidity on surgical-site infection (SSI) rates within a representative data set in the continental United States, 2007–2014. 25 …”
Section: Emerging Infections Driven By Climate Changementioning
confidence: 97%
See 1 more Smart Citation
“…In a data set of 1.6 million infections due to Escherichia coli, Klebsiella pneumoniae , and Staphylococcus aureus , they identified significant associations between antimicrobial resistance patterns in these common pathogens and higher local minimum temperatures. 24 Another recent study similarly showed modest but significant impacts of both local temperature and humidity on surgical-site infection (SSI) rates within a representative data set in the continental United States, 2007–2014. 25 …”
Section: Emerging Infections Driven By Climate Changementioning
confidence: 97%
“…Other factors, however, may contribute to population-level increases in antibiotic resistance including, for example, the overuse of antibiotics in livestock farming. In a 2018 study published in Nature Climate Science , McFadden et al 24 explored the role of climate (temperature, primarily) and other factors on the distribution of antibiotic resistance in human infections across the United States. In a data set of 1.6 million infections due to Escherichia coli, Klebsiella pneumoniae , and Staphylococcus aureus , they identified significant associations between antimicrobial resistance patterns in these common pathogens and higher local minimum temperatures.…”
Section: Emerging Infections Driven By Climate Changementioning
confidence: 99%